Analisis Perbedaan Kinerja Keuangan Bank Umum Milik Negara Konvensional dan Bank Umum Syariah di Indonesia - Sri Yunawati (Al-Buhuts, 2019)
This study aims to to see what there are differences between the financial performance of BUMNN conventional and bank syariah, if reflected in the following the ratio of the CAR , non-performing loans to outstanding loans , ROE , ROA , BOPO, and LDR .In this research put it through statistical analysis of the ratio of descriptive financial used with describing the results of the highest value , the lowest score , the average, and the outcomes of the against a standard deviation, of a variable researched .In this research in conducting statistical testing data processing using kruskal walls, who was one of the probe in statistics non-parametrik who frequently used to test some samples who are not in charge. Based on tests carried out so the results showed that the financial performance of BUMN conventional and Bank Syariah seen from ratio car slightly went up , non-performing loans to outstanding loans, ROE , ROA , BOPO , and LDR there are significant differences.